DAMPAK KEGIATAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PERUSAHAAN SEBAGAI MOTOR PENGGERAK PENINGKATAN EKONOMI MASYARAKAT - Handy Nugroho (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2019)
Every business entity especially a company would want benefit in the form of profit. The profitsobtained by the company must be redistributed, not only to the shareholders but also to the company'sstakeholders, namely the community. One form of distribution of these benefits is through CorporateSocial Responsibility (CSR) activities. At present the activities of Corporate Social Responsibility (CSR)have been carried out by many companies both in the form of physical development and humanresource development. Increased physical development and human resource development throughCSR are expected to help the government to improve the economic welfare of the people in the area,where the company operates and benefits.This literature-based research tries to trace the forms of corporate social responsibility thathave been carried out by various profit-oriented companies and their impact on the improvement of theeconomy of the regional communities around the company. Sources of data used as samples in thisstudy are research papers in the form of journals and papers which relate to the role of corporate socialresponsibility activities carried out by the company towards improving the economy of the people in thearea of the company operating. The results of the various studies carried out are then summarized in ageneral description of whether CSR that has been carried out in Indonesia contributes to improving theeconomy of the community around the company.The results of the literature review that have been carried out based on sample research topicsfound that a large part found there was a significant influence of CSR conducted by the company onimproving the economic welfare of the community. The study also concluded that CSR activities in theform of human resource development have a greater impact on improving the economic welfare of thecommunity. We will hope that in the future with the encouragement of the Government, CSR that willcarried out by the company can focus to prioritizing activities that develops community economic